Somanathapura, Keshava temple, Outer wall of the southern garbhagriha, Sculpture of God Vishnu seated on Adishesha; Hoysala architecture - Lawrence Rodrigues (2021)
Image courtesy: Lawrence Rodrigues - www.yatrikaone.com